Change of phase transformation and bond strength of Y-TZP with various hydrofluoric acid etching - Mi-Kyung Yu; Eun-Jin Oh; Myung-Jin Lim; Kwang-Won Lee (Restorative Dentistry & Endodontics)
ObjectivesThe purpose of this study was to quantify phase transformation after hydrofluoric acid (HF) etching at various concentrations on the surface of yttria-stabilized tetragonal zirconia polycrystal (Y-TZP), and to evaluate changes in bonding strength before and after thermal cycling.Materials and MethodsA group whose Y-TZP surface was treated with tribochemical silica abrasion (TS) was used as the control. Y-TZP specimens from each experimental group were etched with 5%, 10%, 20%, and 40% HF solutions at room temperature for 10 minutes. First, to quantify the phase transformation, Y-TZP specimens (n = 5) treated with TS, 5%, 10%, 20% and 40% HF solutions were subjected to X-ray diffraction. Second, to evaluate the change in bond strength before and after thermal cycling, zirconia primer and MDP-containing resin cement were sequentially applied to the Y-TZP specimen. After 5,000 thermal cycles for half of the Y-TZP specimens, shear bond strength was measured for all experimental groups (n = 10).ResultsThe monoclinic phase content in the 40% HF-treated group was higher than that of the 5%, 10%, and 20% HF-treated groups, but lower than that of TS-treated group (p < 0.05). The 40% HF-treated group showed significantly higher bonding strength than the TS, 5%, and 10% HF-treated groups, even after thermal cycling (p < 0.05).ConclusionsThrough this experiment, the group treated with SiO2 containing air-borne abrasion on the Y-TZP surface showed higher phase transformation and higher reduction in bonding strength after thermal cycling compared to the group treated with high concentration HF.